2011
DOI: 10.1088/0004-637x/744/2/87
|View full text |Cite
|
Sign up to set email alerts
|

Age Spread in W3 Main: Large Binocular Telescope/Luci Near-Infrared Spectroscopy of the Massive Stellar Content

Abstract: We present near-infrared multi-object spectroscopy and JHK s imaging of the massive stellar content of the Galactic star-forming region W3 Main, obtained with LUCI at the Large Binocular Telescope. We confirm 15 OB stars in W3 Main and derive spectral types between O5V and B4V from their absorption line spectra. Three massive Young Stellar Objects are identified by their emission line spectra and near-infrared excess. The color-color diagram of the detected sources allows a detailed investigation of the slope … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(116 citation statements)
references
References 80 publications
10
104
2
Order By: Relevance
“…An age dispersion of a few Myr could also contribute to differences between age measurements made from MS and PMS stars in very young clusters. Star formation in at least some clusters has been found to occur over a 2-3 Myr time period (e.g., Hosokawa et al [2011]; Delgado et al [2011]; Bik et al [2012] and references therein), while in giant star-forming complexes (e.g., De Marchi et al 2011a) in-falling gas may fuel star formation for even more extended periods of time (e.g., Garcia-Benito et al 2011).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…An age dispersion of a few Myr could also contribute to differences between age measurements made from MS and PMS stars in very young clusters. Star formation in at least some clusters has been found to occur over a 2-3 Myr time period (e.g., Hosokawa et al [2011]; Delgado et al [2011]; Bik et al [2012] and references therein), while in giant star-forming complexes (e.g., De Marchi et al 2011a) in-falling gas may fuel star formation for even more extended periods of time (e.g., Garcia-Benito et al 2011).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…By means of K-band spectroscopy, their massive star nature was confirmed and the spectral types of these massive stars have been determined (Bik et al 2012) such that the age of the most massive star (IRS2) could be derived. Based on this age determination (2−3 Myr) and the presence of the very young hypercompact HII regions, Bik et al (2012) concluded that W3 Main has been actively forming stars over the last 2−3 Myr.…”
Section: Introductionmentioning
confidence: 99%
“…This emission, though, is quite narrow and does not affect the wings of the photospheric absorption Brγ lines. Hence the absorption wings can still be used for spectral classification (see Bik et al 2012, for a similar classification procedure). An example of such comparison of the Brγ absorption line wings is shown in Fig.…”
Section: Spectral Classification: Distance and Extinction To Cn15/16/17mentioning
confidence: 99%